Paediatric inflammatory bowel disease in India: a prospective multicentre study. Issue 10 (October 2020) - Srivastava, Anshu; Sathiyasekharan, Malathi; Jagadisan, Barath; Bolia, Rishi; Peethambaran, Maya; Mammayil, Geetha; Acharya, Bhaswati; Malik, Rohan; Sankaranarayanan, Srinivas; Biradar, Vishnu; Malhotra, Smita; Philip, Mathew; et al.
Abstract : Background: Paediatric inflammatory bowel disease (PIBD) is increasing across the world. However, information from India is sparse. This multicentre study evaluated the demographics, clinical phenotype and outcome of PIBD from India. Methods: Data of children (⩽18 years) with PIBD were collected using a proforma containing details of demographics, clinical profile, extraintestinal manifestations (EIM), investigations, disease extent and treatment. Results: Three hundred twenty-five children [Crohn's disease: 65.2%, ulcerative colitis: 28.0%, IBD unclassified (IBDU): 6.7%, median age at diagnosis: 11 (interquartile range 6.3) years] were enrolled. 6.9% children had family history of IBD. Pancolitis (E4) was predominant in ulcerative colitis (57.8%) and ileocolonic (L3, 55.7%) in Crohn's disease. Perianal disease was present in 10.9% and growth failure in 20.9% of Crohn's disease cases. Steroids were the initial therapy in 84.2%, 5-amino salicylic acid in 67.3% and exclusive enteral nutrition (EEN) in 1.3% cases. Overall, immunomodulators and biologics were given to 84.3 and 17.9% cases, respectively, and 2.9% cases underwent surgery. Very early onset IBD (VEOIBD) was seen in 60 (19.2%) children. IBDU was commoner in the VEOIBD than the older-PIBD (18/60 vs 4/253; P < 0.001). VEOIBD-Crohn's disease patients more often had isolated colonic disease than the older Crohn's disease (45.4% vs 11.8%; P < 0.001). Prevalence of perianal disease, EIM, therapeutic requirements and outcome were not different between VEOIBD and older-PIBD. Conclusion: Disease location and phenotype of PIBD in Indian children is similar to the children from the west. However, the therapeutic options of EEN, biologics and surgery are underutilized. VEOIBD accounted for 19.2% of PIBD. Abstract : Supplemental Digital Content is available in the text.